Book Review: Suiting Themselves: How Corporations Drive the Global Agenda. (24th May 2007) - Welford, Richard
Suiting Themselves: How Corporations Drive the Global Agenda, by Sharon Beder. London, Earthscan. ISBN: 1844073319